Jezus przynosi Ewangelię Samarii (J 4,1-42) - Witczyk, Henryk (Verbum Vitae, 2006)
Jesus, speaking with the Sarnacitan woman, and next with the inhabitants of Samaria, fulfills the "work" which he received from his Father to accomplish. In its essence it is a work of revelation and is done giving people "the gift of God" on which are based the gift of the Gospel (Truth) and gift ofthe Holy Spirit (Spirit of Truth). Accepting these two gifts of God from Jesus changes the person and life of the Samaritan woman and the inhabitants of Samaria. Jesus fulfills the, work of revelation, on which the salvation of the world depends, not only in Judea and Galilee, but also among Samaritans, the inheritants of the old kingdom of Israel, who due to difficult histoncal experiences became the followers of a syncretic religion. In reality they did not cease to follow the patriarch Jacob and worship the only God on mount Garizim, however through orthodox believers of Judaism they were considered separated from God and His blessings heralding finał salvation due to their mingling of the revealed religion with cults brought in over the ages from Babylon. Jesus Himself challenged them to hecorne followers of the authentic, new religion - "in the Spirit and in Truth." The author of the fourth Gospel teaches that Jesus "had to" go through Samaria, because in the saving plan of God it was to be that He first meet with the Samaritan woman, and next with the town's inhabitants. They are also called by God to be able to discover in Jesus the "Savior of the world." God, who sent Jesus into the world, is not only God of Israel, although ,,salvation has its beginning from the Jews." God, the Father of Jesus, is also Father of all peoples, beginning with orthodox Israel upholding forages faith in Him as the Only God. Turning to all the nations of the earth with His gifts, God, the Father ofJesus, begins with those who not only geographically but prlmarily through salvation history are closest to Israel - from the Samaritans.